Breit interaction in dielectronic recombination of hydrogenlike xenon ions: storage-ring experiment and theory - Wang, Shu-Xing; Brandau, Carsten; Fritzsche, Stephan; Fuchs, Sebastian; Harman, Zoltán; Kozhuharov, Christophor; Müller, Alfred; Steck, Markus; Schippers, Stefan; Justus Liebig University Giessen (My University, 2024)
Electron-ion collision spectroscopy of the KLL dielectronic recombination (DR) resonances of hydrogenlike xenon ions was performed at a heavy-ion storage ring with a resolving power that is competitive with x-ray spectroscopy of inner-shell transitions in highly charged ions. The KL1/2L1/2, KL1/2L3/2, and KL3/2L3/2 resonance groups and even parts of their fine structure are individually resolved. The resonance strengths were measured on an absolute scale and compared with results from multi-configuration Dirac–Fock (MCDF) calculations. These are in excellent agreement with the experimental findings when QED effects on the resonance energies and the Breit interaction are considered. As already found for DR of hydrogenlike uranium (Bernhardt et al. in Phys Rev A 83:020701(R), 2011), this interaction is particularly strong for the KL1/2L1/2 resonance group. For U91+, it increases the KL1/2L1/2 DR resonance strength by 40%. For Xe53+, the increase is found to amount to 25%, confirming the prediction that the influence of the Breit interaction grows with increasing nuclear charge. A comprehensive appendix treats the derivation of experimental and theoretical merged-beams recombination rate coefficients for interacting beams of relativistic electrons and ions.
Keywords: ddc:530